Textural effect of Pt catalyst layers with different carbon supports on internal oxygen diffusion during oxygen reduction reaction - Zhang, Wenli; Ma, Zhejie; Zhao, Xuankai; Zhou, Liheng; Yang, Liu; Li, Ping (Frontiers in Chemistry, 2023)
One way to address the cost issue of polymer electrolyte membrane fuel cells (PEMFCs) is to reduce the amount of platinum used in the cathode catalyst layers (CLs). The oxygen mass transfer resistance of the cathode CLs is the main bottleneck limiting the polarization performance of low Pt-loading membrane electrodes at high current densities. Pt nanoparticles, ionomers, carbon supports, and water in cathode CLs can all affect their oxygen mass transfer resistance. From the perspective of carbon supports, this paper changed the texture of CLs by adding carbon nanotubes (CNTs) or graphene oxide (GO) into carbon black (XC72) and studied its impact on the oxygen mass transfer resistance. A mathematical model was adopted to correlate total mass transfer resistance and internal diffusion efficiency factor with CL structure parameters in order to determine the dominant textural effect of a CL. The results show that adding 30%CNT or 20GO to carbon black of XC72 improved the electrocatalytic performance and mass transfer capability of the composite carbon-supported Pt catalyst layers during oxygen reduction reaction. The study further reveals that the smaller particle-sized carbon material with tiny Pt nanoparticles deposition can minimize the internal oxygen diffusion resistance. A less dense CL structure can reduce the oxygen transfer resistance through the secondary pores. The conclusion obtained can provide guidance for the rational design of optimal cathode CLs of PEMFCs.